State of oral hygiene and identification of the main risk factors for inflammatory diseases of periodontal tissues in young people. - Makarenko, M. V. (Medicni Perspektivi, 2014)
A high percentage of prevalence of inflammatory periodontal diseases in young age causes urgency of treatment and prevention of inflammatory diseases of periodontal tissue in young age. Therefore, the research purpose was to investigate the hygienic condition and identification of the main risk factors for gingivitis in patients aged 18-30 years. 286 people aged from 18 to 30 years were observed in the study. To assess hygienic condition of the oral cavity and to determine the thickness of plaque indices OHI-S (simplified oral hygiene index Green Vermilyona) and Silness Loe were used. Studies of oral hygiene status suggests that in patients with different etiologies of periodontal tissue inflammation, oral hygienic condition ranged from "satisfactory" to "poor." Therefore the results of study of hygiene and periodontal indices and samples confirmed presence of moderately expressed inflammation in the gums in young adults with chronic catarrhal gingivitis. Most often inflammation in the gums, namely, chronic catarrhal gingivitis was determined in patients with fixed prosthesis designs in the mouth or in violation of the bite, related to the major risk factors for periodontal disease occurring in young adults aged from 18 to 30 years.